Literasi Sains: Cinta Lingkungan Untuk Peserta Didik SD I Watujara - Wardatun Jaelani; Nining Sar’iyyah; Adi Neneng Abdullah; Vinsensius Mbabho (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this activity is to improving environmental literacy in elementary schools. Environmental science literacy is a combination of science concepts and the development of positive attitudes towards nature. This activity was carried out at SDI Watujara, involving students in grades IV, V, V. The method used in this service activity is in the form of situation analysis, socialization approach, problem identification, determining work objectives, implementing activities and evaluating the results of activities. The results of the activity showed an increase in the understanding of SDI Watujara students regarding the conceptions related to the theme of environmental love. The results of this service provide a basis for implementing similar programs in other schools and show the potential of PKM programs in facilitating the development of science literacy and environmental awareness among students. The conclusion of this research is expected to motivate relevant parties to integrate science literacy programs on environmental love at the elementary level to achieve a broader positive impact.